USM FINE ARTS ALUMNI ORGANISES ‘SENI SPEKTRUM’ EXHIBITION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 12 June 2016 – 14 Universiti Sains Malaysia (USM) alumni members with a background in Fine Arts recently returned to the campus to hold the ‘Seni Spektrum’ exhibition and also organised the ExUSM Fine Art 19992001 Reunion at the Muzium dan Galeri Tuanku Fauziah (MGTF) in USM